University in America Latina, transdiscipline and networks of research collaborative (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2016)
The higher education system distributes its core functions in multiple areas, but without a doubt, they are recognized and important within the academic world some such as teaching, research, extension, the social projection, the development of talent, among others according to the strategic definitions and priorities of the education, science, technology and innovation system in each country. Currently, is rethinks approach to these activities from updated outlooks, subject to realities and emerging issues of context, prioritizing processes pooled between researchers and transdisciplinary networks. In the last two decades, research in Latin America has been organized around networks cooperative and innovative, that is, in order to promote the achievement of theoretical results or in practice, this being an important dynamic axis in the production of knowledge. In this context, are inserted needs of development social, economic, political, to the know popular and to the production scientific, that not only presented from them different looks of knowledge and experiences, but also from several logical of interpretation, unveiling so, them practices socializing that must be addressed taking into account their differences and contradictions to be exceeded of way inclusive, global and plural. It is essential then, a science to the service of the society and in collaboration among peers, to boost relations solidary, plural, with collective learning, indigenous and interdisciplinary. The present dissertation aims to reveal the university practice from collaborative, interdisciplinary, research through the work of networks of research and academic. The method facilitates the literature review and constructive perspective enables the necessary dialogic between groups of researchers and complex networks. It is concluded that evidence of some experiences of research networks, privilege complex action from different realities and joint solutions.
Keywords: university; transdiscipline; complexity; research and academic networks